Measurement of the forward-backward asymmetry of top-quark and antiquark pairs using the full CDF Run II data set - Aaltonen, T.; Amerio, S.; Amidei, D.; Anastassov, A.; Annovi, A.; Antos, J.; Apollinari, G.; Appel, J. A.; Arisawa, T.; Artikov, A.; Asaadi, J.; Ashmanskas, W.; et al. (My University, 2016)
We measure the forward-backward asymmetry of the production of top-quark and antiquark pairs in proton-antiproton collisions at center-of-mass energy s=1.96 TeV using the full data set collected by the Collider Detector at Fermilab (CDF) in Tevatron Run II corresponding to an integrated luminosity of 9.1 fb-1. The asymmetry is characterized by the rapidity difference between top quarks and antiquarks (?y) and measured in the final state with two charged leptons (electrons and muons). The inclusive asymmetry, corrected to the entire phase space at parton level, is measured to be AFBtt=0.12±0.13, consistent with the expectations from the standard model (SM) and previous CDF results in the final state with a single charged lepton. The combination of the CDF measurements of the inclusive AFBtt in both final states yields AFBtt=0.160±0.045, which is consistent with the SM predictions. We also measure the differential asymmetry as a function of ?y. A linear fit to AFBtt(|?y|), assuming zero asymmetry at ?y=0, yields a slope of ?=0.14±0.15, consistent with the SM prediction and the previous CDF determination in the final state with a single charged lepton. The combined slope of AFBtt(|?y|) in the two final states is ?=0.227±0.057, which is 2.0? larger than the SM prediction. © 2016 American Physical Society.
Citation: Aaltonen, T., Amerio, S., Amidei, D., Anastassov, A., Annovi, A., Antos, J., . . . Zucchelli, S. (2016). Measurement of the forward-backward asymmetry of top-quark and antiquark pairs using the full CDF Run II data set. Physical Review D - Particles, Fields, Gravitation and Cosmology, 93(11). doi:10.1103/PhysRevD.93.112005